Determination of the concentration of ions and electrons in a low-temperature and pulsed plasma flow based on the probe theory - Нурбердиев, Алимардан; Сейтханова, Айнур; Тасуов, Болат (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2025)
Although plasma is the fourth state of matter and a quasi-neutral medium, we usually consider plasma as having high and low temperatures, equilibrium and nonequilibrium, ideal and non-ideal. Accordingly, we need to use different methods and tools to study them. However, in this article, we will show that the same research theory can be applied to some types of artificial plasma, or we will use another method to check the obtained physical quantities. As a result of studies using the electric probe method, the concentration of ions and electrons in low-temperature plasma (glow discharge) was determined. In laboratory conditions, a cylindrical electric probe can be used to record the volt-ampere characteristics. In addition, the energy of ions in a pulsed plasma flow was determined using a Faraday cup. The charges entering the Faraday cup collide with the surface of the inner electrode. As a result, we register the current generated in the electric circuit using an oscilloscope. There are several methods for determining the ion concentration using a Faraday cup. But we will use the theory associated with the electric probe in studying low temperatures. In this paper, we will prove that plasma is a quasi-neutral medium using equations to calculate the composition of plasma.